2019
DOI: 10.1016/j.ijrobp.2019.06.1811
|View full text |Cite
|
Sign up to set email alerts
|

Dose Response Relationship and Prognostic Factors of Nodal Control Rate of Metastatic Lymph Nodes in Cervical Cancer

Abstract: without metastatic disease, 22 underwent upfront surgery or radiotherapy followed by adjuvant concurrent chemo-radiotherapy (CCRT) or chemotherapy (the local first group); 7 underwent CCRT or chemotherapy before surgery(NAC group); 12 underwent surgery alone, and the remaining 10 underwent CCRT alone. Chemotherapy was administered to 53 (80%) patients. Among the 53 patients, 37 underwent chemo-regimen for small cell carcinoma (CDDP/CBDCA+VP16 or CPT11), whereas the remaining 16 patients underwent chemo-regimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The coincidence rate between the results of CT examination and pathological examination in these patients is high. When using spiral CT to examine patients with cervical cancer, the diameter of their lymph nodes can be measured on the cross-section, and then, the shape and location of lymph nodes can be reconstructed [ 25 ]. However, when this method is used to examine patients with cervical cancer, it has poor ability to distinguish the internal structure of lymph nodes and low sensitivity to lymph nodes with metastasis but small volume, especially lymph nodes with a diameter of less than 10 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The coincidence rate between the results of CT examination and pathological examination in these patients is high. When using spiral CT to examine patients with cervical cancer, the diameter of their lymph nodes can be measured on the cross-section, and then, the shape and location of lymph nodes can be reconstructed [ 25 ]. However, when this method is used to examine patients with cervical cancer, it has poor ability to distinguish the internal structure of lymph nodes and low sensitivity to lymph nodes with metastasis but small volume, especially lymph nodes with a diameter of less than 10 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also identified improved nodal control or OS with increasing dose. The reported LN size thresholds for benefit have ranged from ≥1.5 to 2.4 cm [ 1 , 14 , 19 - 23 ]. The number of positive nodes, LN SUV (standardized uptake value) heterogeneity, maximum LN SUV, and various other factors have demonstrated prognostic value [ 4 , 18 , 24 - 27 ].…”
Section: Discussionmentioning
confidence: 99%